Reactivity studies of carbon, phosphorus and sulfur‐based acyl sites with tertiary oximes in gemini surfactants. (18th June 2013) - Gupta, Bhanushree; Sharma, Rahul; Singh, Namrata; Karpichev, Yevgen; Satnami, Manmohan L.; Ghosh, Kallol K.
<x xml:space="preserve">Abstract</x> Kinetic studies of the reactions of tertiary oximes (monoisonitroso acetone; MINA and butane 2, 3 dione monooxime; BDMO) with some carboxylate (p‐nitrophenyl acetate and p‐nitrophenyl benzoate), phosphate (p‐nitrophenyl diphenyl phosphate and bis (2, 4‐dinitrophenyl) phosphate) and sulfonate (p‐nitrophenyl p‐toluene sulphonate) esters in gemini surfactants have been conducted. The observed first‐order rate constant versus surfactant profiles show micelle‐assisted bimolecular reactions involving interfacial ion exchange between bulk aqueous media and micellar pseudophase. Experimental results showed that MINA exhibited better nucleophilic activity towards ester cleavage than BDMO. Pseudophase model has been applied in order to determine micellar second‐order rate constants and binding constants. Copyright © 2013 John Wiley & Sons, Ltd.